Cardiac Complications of Propionic and Other Inherited Organic Acidemias - Park, Kyung Chan; Krywawych, Steve; Richard, Eva; Desviat, Lourdes R.; Swietach, Pawel (Frontiers in Cardiovascular Medicine, 2020)
Clinical observations and experimental studies have determined that systemic acid-base disturbances can profoundly affect the heart. A wealth of information is available on the effects of altered pH on cardiac function but, by comparison, much less is known about the actions of the organic anions that accumulate alongside H+ ions in acidosis. In the blood and other body fluids, these organic chemical species can collectively reach concentrations of several millimolar in severe metabolic acidoses, as in the case of inherited organic acidemias, and exert powerful biological actions on the heart that are not intuitive to predict. Indeed, cardiac pathologies, such as cardiomyopathy and arrhythmia, are frequently reported in organic acidemia patients, but the underlying pathophysiological mechanisms are not well established. Research efforts in the area of organic anion physiology have increased dramatically in recent years, particularly for propionate, which accumulates in propionic acidemia, one of the commonest organic acidemias characterized by a high incidence of cardiac disease. This Review provides a comprehensive historical overview of all known organic acidemias that feature cardiac complications and a state-of-the-art overview of the cardiac sequelae observed in propionic acidemia. The article identifies the most promising candidates for molecular mechanisms that become aberrantly engaged by propionate anions (and its metabolites), and discusses how these may result in cardiac derangements in propionic acidemia. Key clinical and experimental findings are considered in the context of potential therapies in the near future.